[Use of Kovaltry® in patients with Hemophilia A: clinical and economical aspects from the pivotal clinical trials] - D'Angiolella, Lucia Sara; Molinari, Angelo Claudio; Cortesi, Paolo Angelo; Coppola, Antonio; Mantovani, Lorenzo Giovanni (Farmeconomia. Health Economics and Therapeutic Pathways, 2017)
[Article in Italian]